Some aspects of the changes in the task and results of the mathematics state maturity exam in 2012–2021 - Pranaitytė, Gabija; Narkevičienė, Bronė (Lietuvos matematikos rinkinys, 2022)
In this work, the aspects of the task of the state maturity exam in mathematics (structure and content of the program) and the change of students’ achievements (difficulty of the tasks and differentiating factor) in 2012–2021 are analyzed. Between 2012 and 2021, the exam program changed once (in 2014; implemented since 2015). The changes in content were minor in all four topic areas. There were structural changes in the types of exam tasks: the number of open-ended questions increased, while the number of multiple-choice and short task questions decreased. Changes in both content and structure were reflected in some changes in outcomes of the exam. Only one statistical difference between the difficulty of the exam (2017 and 2020 exams, which were the easiest and most difficult in 2012–2021, respectively) has been observed.